2019
DOI: 10.2337/dc18-0828
|View full text |Cite
|
Sign up to set email alerts
|

Eye Care Utilization Among Insured People With Diabetes in the U.S., 2010–2014

Abstract: OBJECTIVEDiabetic retinopathy (DR) is the leading cause of blindness among working-age adults, and although screening with eye exams is effective, screening rates are low. We evaluated eye exam visits over a 5-year period in a large population of insured patients 10-64 years of age with diabetes. RESEARCH DESIGN AND METHODSWe used claims data from IBM Watson Health to identify patients with diabetes and continuous insurance coverage from 2010 to 2014. Diabetes and DR were defined using ICD-9 Clinical Modificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
47
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(51 citation statements)
references
References 22 publications
(14 reference statements)
3
47
1
Order By: Relevance
“…Consistent with previous studies [9,13,14], older age was associated with eye care utilization among people with diabetes. Specifically, people aged 55 years and above were more likely to utilize eye care services.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Consistent with previous studies [9,13,14], older age was associated with eye care utilization among people with diabetes. Specifically, people aged 55 years and above were more likely to utilize eye care services.…”
Section: Discussionsupporting
confidence: 91%
“…The rates of eye care utilization among people with diabetes have been reported in different population-based studies [ 9 12 ]. For example, in the United States, both Benoit et al [ 9 ] and MacLennan et al [ 13 ] reported that nearly half of all patients with diabetes had not had an eye exam in over 5 years. In a hospital-based study in India, Sreenivas et al [ 12 ] reported that about a third of diabetic patients sampled had accessed eye care services in the last 1 year.…”
Section: Discussionmentioning
confidence: 99%
“…Although DRS is found to be effective, uptake is often suboptimal [13][14][15][16][17][18]. In Ireland, RetinaScreen provides free, annual retinal screening (and if necessary, treatment) to anyone aged 12 years or older with diagnosed diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, a study from Japan using claims data found an annual utilization rate of 95.8% 38. For eye examination, studies in the USA reported utilization rates of 15.3% (using claims data),39 70% (using telephone survey data),40 and 75% (data from rural Latinos) 41. A Japanese study reported a utilization rate of 35.6%,38 and the rate in the Italian study was even lower (15.6%) 37.…”
Section: Discussionmentioning
confidence: 93%